PELAKSANAAN PROGRAM PEMBERDAYAAN USAHA EKONOMI PRODUKTIF (UEP) SUKU DINAS SOSIAL JAKARTA BARAT UNTUK PENINGKATAN KESEJAHTERAAN FAKIR MISKIN DI KECAMATAN TAMBORA - Nur Ilham; Muhtadi Muhtadi (Jurnal Kommunity Online, 2023)
The purpose of this study was to determine the process and stages of empowerment activities, the impact of the program as well as the supporting and inhibiting factors of the UEP empowerment program in improving welfare. The subjects in this study were eight people, three from the West Jakarta Social Service and five from the beneficiaries of the UEP empowerment program in Tambora District. This research is a descriptive qualitative research. Data collection techniques in this study used interview, observation, and documentation studies. The results of this study indicate that the empowerment of the UEP of the West Jakarta Social Service in increasing the poor in Tambora District has been able to improve welfare through the UEP program with a felt impact on the five beneficiaries of the UEP program. This can be seen from the lives of the five beneficiaries in Tambora District which are in accordance with the existing indicators of success. The indicators for the success of the UEP program include economic impacts, social impacts, and administrative impacts. The three success indicators have been in accordance with the increased welfare felt by the five beneficiaries.